Repertoire and Diversity of Toxin – Antitoxin Systems of Crohn’s Disease-Associated Adherent-Invasive Escherichia coli. New Insight of T his Emergent E. coli Pathotype - Bustamante, Paula; Vidal, Roberto (Frontiers in Microbiology, 2020)
Adherent-invasive Escherichia coli (AIEC) corresponds to an E. coli pathovar proposed as a possible agent trigger associated to Crohn’s disease. It is characterized for its capacity to adhere and to invade epithelial cells, and to survive and replicate inside macrophages. Mechanisms that allow intestinal epithelium colonization, and host factors that favor AIEC persistence have been partly elucidated. However, bacterial factors involved in AIEC persistence are currently unknown. Toxin-antitoxin (TA) systems are recognized elements involved in bacterial persistence, in addition to have a role in stabilization of mobile genetic elements and stress response. The aim of this study was to elucidate the repertoire and diversity of TA systems in the reference AIEC NRG857c strain and to compare it with AIEC strains whose genomes are available at databases. In addition, toxin expression levels under in vitro stress conditions found by AIEC through the intestine and within the macrophage were measured. Our results revealed that NRG857c encodes at least 33 putative TA systems belonging to type I, II, IV and V, distributed around all the chromosome, and some in close proximity to genomic islands. A TA toxin repertoire marker of the pathotype was not found and the repertoire of 33 TA toxin genes described here was exclusive of the reference strains, NRG857c and LF82. Most toxin genes were upregulated in the presence of bile salts and acidic pH, as well as within the macrophage. However, different transcriptional responses were detected between reference strains (NRG857c and HM605), recalling the high diversity associated to this pathotype. To our knowledge this is the first analysis of TA systems associated to AIEC and it has revealed new insight associated to this emergent E. coli pathotype.